Leukocyte-Reduced Platelet-Rich Plasma Alters Protein Expression of Adipose Tissue–Derived Mesenchymal Stem Cells. Issue 2 (August 2016) - Loibl, Markus; Lang, Siegmund; Hanke, Alexander; Herrmann, Marietta; Huber, Michaela; Brockhoff, Gero; Klein, Silvan; Nerlich, Michael; Angele, Peter; Prantl, Lukas; Gehmert, Sebastian
Abstract : Background: Application of platelet-rich plasma and stem cells has become important in regenerative medicine. Recent literature supports the use of platelet-rich plasma as a cell culture media supplement to stimulate proliferation of adipose tissue–derived mesenchymal stem cells. The underlying mechanism of proliferation stimulation by platelet-rich plasma has not been investigated so far. Methods: Adipose tissue–derived mesenchymal stem cells were cultured in α-minimal essential medium supplemented with platelet-rich plasma or fetal calf serum. Cell proliferation was assessed with cell cycle kinetics using flow cytometric analyses after 48 hours. Differences in proteome expression of the adipose tissue–derived mesenchymal stem cells were analyzed using a reverse-phase protein array to quantify 214 proteins. Complementary Ingenuity Pathways Analysis and gene set enrichment analysis were performed using protein data, and confirmed by Western blot analysis. Results: A higher percentage of adipose tissue–derived mesenchymal stem cells in the S phase in the presence of platelet-rich plasma advocates the proliferation stimulation. Ingenuity Pathways Analysis and gene set enrichment analysis confirm the involvement of the selected proteins in the process of cell growth and proliferation. Ingenuity Pathways Analysis revealed a participation in the top-ranked canonical pathways PI3K/AKT, PTEN, ILK, and IGF-1. Gene set enrichment analysis identified the authors' protein set as being part of significantly regulated protein sets with the focus on cell cycle, metabolism, and the Kyoto Encyclopedia of Genes and Genomes transforming growth factor-β signaling pathway. Conclusions: The present study provides evidence that platelet-rich plasma stimulates proliferation and induces a unique change in the proteomic profile of adipose tissue–derived mesenchymal stem cells. The interpretation of altered expression of regulatory proteins represents a step forward toward achieving good manufacturing practice–compliant criteria for cell-based strategies. Abstract : Supplemental Digital Content is available in the text.